THE EFFECTIVENESS OF E-STORY TO ENHANCE READING ALOUD FOR STUDENTS OF IMMANUEL 2 ELEMENTARY SCHOOL - Stevani Indrayani; Yohanes Gatot Sutapa Yuliana; Dewi Novita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to determine whether the use of digital media in the form of E-stories affects the reading aloud skills of fifth-grade students at Immanuel 2 Elementary School. The research employed a quantitative method using a pre-experimental design with one group pre-test and post-test. The sample consisted of 35 fifth-grade students. The instruments used in this study was reading aloud test. During the treatment, students participated in two scaffolded E-story sessions involving digital storytelling, guided reading, and group practice using selected sentences containing target keywords. The data analysis revealed a t-value of 28.25 and an effect size of 0.087 for the effectiveness test, indicating a very strong effect. indicating a significant difference between students’ reading performance before and after the treatment. It can be concluded that the use of E-story is effective for students’ reading aloud. Therefore, E-stories can serve as an effective alternative to enhance reading aloud elementary school students.